2010
DOI: 10.1002/jor.21172
|View full text |Cite
|
Sign up to set email alerts
|

Improving between‐day kinematic reliability using a marker placement device

Abstract: 3D motion analysis is commonly used to measure clinical outcomes, involving repeated measures over time. However, the dayto-day reliability of these measurements has been questioned and few attempts have been made to improve this reliability. Our purpose was to determine if a marker placement device (MPD) could improve day-to-day kinematic reliability as compared to manual marker placement. Ten healthy runners participated. Day-to-day comparisons of peak angles were made between manual marker placement and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 12 publications
2
57
3
Order By: Relevance
“…For example Noehren et al [17] reported SEM values for sagittal motion of the hip (5.1°), knee (1.9°) and ankle (1.4°) for peak excursion, suggesting slightly better reproducibility than the current study. This difference may be attributed to the higher speeds used in this study which may have resulted in relatively high levels of within-day variability.…”
Section: Lower Levels Of Between-day Reproducibility Were Observed Incontrasting
confidence: 50%
“…For example Noehren et al [17] reported SEM values for sagittal motion of the hip (5.1°), knee (1.9°) and ankle (1.4°) for peak excursion, suggesting slightly better reproducibility than the current study. This difference may be attributed to the higher speeds used in this study which may have resulted in relatively high levels of within-day variability.…”
Section: Lower Levels Of Between-day Reproducibility Were Observed Incontrasting
confidence: 50%
“…Lastly, a rigid clusters of four tracking markers were placed on the distal, posterolateral thigh and distal shank. The positions of the anatomical markers were recorded using a marker placement device 21. These measurements were then used to place the anatomical markers for each subsequent data collection.…”
Section: Methodsmentioning
confidence: 99%
“…. 30 At the final data collection, anatomical markers were mounted according to the baseline coordinates.…”
Section: Baseline Screeningmentioning
confidence: 99%